The Impact of FOMO (Fear of Missing Out) and Impulse Buying on Online Purchasing Decisions on TikTok E-Commerce - Umi Kulsum; Ima Amaliah; Nunung Nurhayati (PT. Anagata Sembagi Education, 2025)
The Explosive Popularity of TikTok Shop as a Social Commerce Platform Has Created a Dynamic and Impulsive Shopping Ecosystem. Its unique characteristics, such as personalized recommendation algorithms, livestream commerce, and viral short-form video content, are strongly suspected to trigger the psychological phenomena of Fear of Missing Out (FOMO) and Impulse Buying, which ultimately influence online Purchasing Decisions. This study aims to analyze the influence of FOMO on Purchasing Decisions on TikTok Shop, with Impulse Buying as a mediating variable. This research uses an explanatory quantitative approach with a survey method. Data was collected through an online questionnaire distributed to 427 active TikTok Shop users in Indonesia who had made a purchase. The data were analyzed using variance-based Structural Equation Modeling (SEM) technique with the help of SmartPLS 4.0 software to test the direct and indirect relationships between variables. The results prove that all proposed hypotheses were accepted. FOMO was proven to have a positive and significant direct effect on Impulse Buying (β = 0.683) and on Purchasing Decisions (β = 0.294). Critically, Impulse Buying was also proven to mediate the effect of FOMO on Purchasing Decisions with a strong indirect effect (β = 0.370). This research model was able to explain 62.8% of the variance in Purchasing Decisions (R² = 0.628), indicating high predictive power. It is concluded that FOMO and Impulse Buying are dominant determining factors in Purchasing Decisions on TikTok Shop. These findings reveal the psychological mechanisms behind the platform's success, where FOMO acts as a powerful initial trigger to create impulsive shopping urges, which then becomes the primary mechanism driving the realization of a purchase decision. This research provides an important contribution to the understanding of consumer behavior in the era of algorithm-driven social commerce.